2002
DOI: 10.1155/2002/682753
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis by reductive cleavage with LiAlH4 of an allyl ether choline‐phospholipid, archaetidylcholine, from the hyperthermophilic methanoarchaeon Methanopyrus kandleri

Abstract: A choline-containing phospholipid (PL-4) in Methanopyrus kandleri cells was identified as archaetidylcholine, which has been described by Sprott et al. (1997). The PL-4 consisted of a variety of molecular species differing in hydrocarbon composition. Most of the PL-4 was acid-labile because of its allyl ether bond. The identity of PL-4 was confirmed by thin-layer chromatography followed by positive staining with Dragendorff reagent and fast-atom bombardment-mass spectrometry. A new method of LiAlH4 hydrogenoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Monounsaturated archaeols were shown to originate from hydroxyarchaeol under acidic conditions as laboratory conversion products (9). However, recent studies described this compound as a constitutive membrane lipid of the hyperthermophilic methanogen Methanopyrus kandleri (28). Under the conditions used in this study (mild alkaline hydrolysis), conversion of hydroxyarchaeol to unsaturated archaeol has not been reported and was successfully applied to analysis of hydroxyarchaeol-containing samples (25,36).…”
mentioning
confidence: 83%
“…Monounsaturated archaeols were shown to originate from hydroxyarchaeol under acidic conditions as laboratory conversion products (9). However, recent studies described this compound as a constitutive membrane lipid of the hyperthermophilic methanogen Methanopyrus kandleri (28). Under the conditions used in this study (mild alkaline hydrolysis), conversion of hydroxyarchaeol to unsaturated archaeol has not been reported and was successfully applied to analysis of hydroxyarchaeol-containing samples (25,36).…”
mentioning
confidence: 83%
“…The results were almost consistent with the hydrocarbon composition described as above. 34) This was the first example of estimation of molecular species composition of archaeal ether phospholipid. In addition to archaetidylcholine, six phospholipids, including phosphorylated N-acetylglucosaminyl archaeol, archaetidylinositol, hydroxyarchaetidylserine, hydroxyarchaetidylethanolamine or unsaturated archaetidylglycerol, A, C40 isoprenoid with three cyclopentane rings at an unusual position; 23) B, C31 non-isoprenoid hydrocarbon with three methyl branches; 25) C, C30 non-isoprenoid hydrocarbon with a cyclopentane ring; 25) D, C35 hybrid hydrocarbon apparently formed by combination of C20 isoprenoid and iso-branched C15 non-isoprenoid hydrocarbon; 25) E, cyclic archaeol with two cylopentane rings.…”
Section: Allyl Ether Type Core Lipids From Methanopyrus Kandleri and mentioning
confidence: 97%
“…But Sprott et al 33) have shown the presence of unsaturated archaeol-based phospholipids, the most abundant of which is unsaturated archaetidylcholine, in the same archaeon by MS of total lipids. Nishihara et al 34) reexamined HCl-methanolysis for choline-containing phospholipids, and they found that most of the phospholipids were degraded during methanolysis but that a small amount of the lipid remained intact, composed of saturated archaeol as a core. They assumed that the aciddegraded portion of the phospholipids was composed of acid-labile allyl ether core lipids.…”
Section: Allyl Ether Type Core Lipids From Methanopyrus Kandleri and mentioning
confidence: 99%
See 2 more Smart Citations